CONTROL OF THE WEEVIL WITH Beauveria sp. IN STORED CORN (Nativa, 2024)
ABSTRACT: The corn weevil (Pagiocerus sp.) is a pest of economic importance stored in corn grains (Zea mays L.). Their control is realized with systemic insecticides, which can cause resistant insects. To search for a biological control method, the entomopathogenic fungus Beauveria was evaluated by spraying stored corn grains attacked by Pagiocerus. The results indicated the pre-insect placement application of the native strain of Beauveria sp. with a dosage of 3 mL-1, it reached 100% insect mortality, while the commercial strain reached 83% mortality. The percentage of damaged grains for the native isolate was 26% and 56% for the commercial isolate with pre-insect placement application of 3 mL-1, unlike the control treatment that reached 80% of damaged grains. The weight loss of grains with the pre-insect placement application of the native isolate with a dosage of 3 mL-1 registered the lowest percentage at 29.9%. In contrast, the commercial isolate registered a weight loss of 56.2%, unlike the control treatment, which registered 85.2%. The study demonstrated that Beauveria applied in suspension with concentrations of 1 x 108 conidia mL-1 can control Pagiocerus for stored corn grains.Keywords: Pagiocerus sp.; Zea mays L.; mortality; biological control; entomopathogen.  Controle do gorgulho do milho com Beauveria sp. Em milho armazenado  RESUMO: O gorgulho do milho (Pagiocerus sp.) é uma praga de importância económica armazenada em grãos de milho (Zea mays L.). Seu controle é realizado com inseticidas sistêmicos, que podem causar insetos resistentes. Na busca de um método de controle biológico, o fungo entomopatogênico Beauveria foi avaliado através da pulverização de grãos de milho armazenados atacados por Pagiocerus. Os resultados indicaram a aplicação preventiva da cepa nativa de Beauveria sp. Na dosagem de 3 mL, atingiu 100% de mortalidade dos insetos, enquanto a cepa comercial atingiu 83% de mortalidade. A porcentagem de grãos danificados para o isolado nativo foi de 26% e 56% para o isolado comercial com aplicação preventiva de 3 mL-1, ao contrário do tratamento controle que atingiu 80% de grãos danificados. A perda de peso dos grãos com a aplicação preventiva do isolado nativo com dosagem de 3 mL registrou a menor porcentagem com 29.9%, enquanto o isolado comercial registrou uma perda de peso de 56.2%, ao contrário do tratamento controle que registrou 85.2%. O estudo demonstrou que Beauveria, aplicada em suspensão com concentrações de 1 x 108 conídios mL-1 pode ser usada preventiva e curativamente como um biocontrolador eficaz de Pagiocerus para grãos de milho armazenados.Palavras chave: Pagiocerus sp.; Zea mays L.; mortalidade; controle biológico; entomopatogênico.